Development and validation of a large, modular test meal with liquid and solid components for assessment of gastric motor and sensory function by non‐invasive imaging. Issue 4 (10th February 2016) - Parker, H. L.; Tucker, E.; Hoad, C. L.; Pal, A.; Costigan, C.; Hudders, N.; Perkins, A.; Blackshaw, E.; Gowland, P.; Marciani, L.; Fox, M. R.
Abstract: Background: Current investigations of stomach function are based on small test meals that do not reliably induce symptoms and analysis techniques that rarely detect clinically relevant dysfunction. This study introduces the large 'Nottingham Test Meal' (NTM) for assessment of gastric motor and sensory function by non‐invasive imaging. Methods: NTM comprises 400 mL liquid nutrient (0.75 kcal/mL) and 12 solid agar‐beads (0 kcal) with known breaking strength. Gastric fullness and dyspeptic sensations were documented by 100 mm visual analogue scale (VAS). Gastric emptying (GE) were measured in 24 healthy volunteers (HVs) by gastric scintigraphy (GS) and magnetic resonance imaging (MRI). The contribution of secretion to gastric volume was assessed. Parameters that describe GE were calculated from validated models. Inter‐observer agreement and reproducibility were assessed. Key Results: NTM produced moderate fullness (VAS ≥30) but no more than mild dyspeptic symptoms (VAS <30) in 24 HVs. Stable binding of meal components to labels in gastric conditions was confirmed. Distinct early and late‐phase GE were detected by both modalities. Liquid GE half‐time was median 49 (95% CI: 36–62) min and 68 (57–71) min for GS and MRI, respectively. Differences between GS and MRI measurements were explained by the contribution of gastric secretion. Breaking strength for agar‐beads was 0.8 N/m 2 such that median 25 (8–50) % intact agar‐beads and 65 (47–74) % solid material remained at 120 min on MRI and GS, respectively. Good reproducibility for liquid GE parameters was present and GE was not altered by agar‐beads. Conclusions & Inferences: The NTM provided an objective assessment of gastric motor and sensory function. The results were reproducible and liquid emptying was not affected by non‐nutrient agar‐beads. The method is potentially suitable for clinical practice. Abstract : Current investigations of stomach function are based on relatively small test meals that do not induce symptoms and analysis techniques that may not detect clinically relevant dysfunction. This study provides validation and development data for studies of gastric motor and sensory function by the 400 mL modular liquid/solid 'Nottingham Test Meal'. The meal is well‐tolerated and potentially suitable for application with non‐invasive imaging in clinical practice.